Gene transfer: DNA microinjection compared with DNA transfection with a very high efficiency. - Shen, Y M (1982)
We have developed a procedure that gives a very high efficiency of transfection in mammalian cells with low-molecular-weight DNA (approximately 10(4) base pairs). The procedure uses cells in suspension that are shocked with polyethylene glycol 4 h after replating. We compared this transfection technique to the standard technique involving manual microinjection of DNA into the nuclei of mammalian cells, using recombinant plasmids containing the simian virus 40 A gene or the herpes simplex virus thymidine kinase gene or both. The efficiency of transfection depends on a number of variables, the most important of which is the difference in transfectability of different cell lines. In our laboratory, the cell line that had the highest efficiency of transfection was tk-ts13, which is derived from baby hamster kidney cells that are deficient in thymidine kinase and temperature sensitive for growth. Under the appropriate conditions, as many as 70% of these cells can be transfected so that transient gene expression can be detected. With the manual microinjection technique, gene expression is independent of the cell line used and occurs faster than after transfection. The results suggest that the critical stage in transfection is the delivery of DNA molecules to the nucleus. Our experiments also indicate that an enzymatic function, in our case, thymidine kinase activity, gives a higher percentage of positive transfectants than when proteins are visualized only by indirect immunofluorescence. The transfection procedure described in this paper is simple and reproducible and, although less efficient than microinjection, ought to be useful in phenotypic and genotypic studies in which transfer of genes to a large number of cells is desirable.